Study on Vibration Influence of Elevated Metro Track Based on Investigation and Measurement - Bo SONG; Hui ZHANG; Chenzhao HUYAN; Yang LI; Guojun FENG (机车电传动)
Taking some one subway viaduct in Beijing city as the object of study, the vibration influence of the operation of the elevated track trains on the surrounding environment was discussed by field measurement, questionnaire research methods. Combined with human body feeling limit of the vibration exposure, the vibration influence of the elevated rail transit was evaluated and analyzed. The results showed that the influence of the orbital vibration was gradually weakened when the distance from the base point increased by means of taking the position of the viaduct as the base point, and the vibration component parallel to the train operation direction was the main influencing factor of the horizontal direction vibration response. Combined with different bridge pier field measurement results, the time of occurrence of the vibration acceleration peak has a certain lag. Phase difference factors should be considered necessarily in the evaluation of the environmental impact of elevated rail vibration. For the case that there is a big difference between the sensation and the measurement, the results of on-site monitoring should be taken as the main basis for vibration impact assessment.Based on the whole body vibration evaluation standard, the planning rationality of the buildings near viaduct was verified, which provided a favorable reference for regional planning around the viaduct.